2021
DOI: 10.3390/pharmaceutics13081139
|View full text |Cite
|
Sign up to set email alerts
|

Functional Duality of Chondrocyte Hypertrophy and Biomedical Application Trends in Osteoarthritis

Abstract: Chondrocyte hypertrophy is one of the key indicators in the progression of osteoarthritis (OA). However, compared with other OA indications, such as cartilage collapse, sclerosis, inflammation, and protease activation, the mechanisms by which chondrocyte hypertrophy contributes to OA remain elusive. As the pathological processes in the OA cartilage microenvironment, such as the alterations in the extracellular matrix, are initiated and dictated by the physiological state of the chondrocytes, in-depth knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 176 publications
(192 reference statements)
1
9
0
Order By: Relevance
“…Further study is needed to fully understand the active components in WG that synergistically act on chondrocyte hypertrophy related OA. However, hypertrophy involves morphologic changes such as enlargement of cells with an increase in apoptotic rate [81]. An in vivo study with morphological evidence may have strengthened our results.…”
Section: Discussionsupporting
confidence: 67%
“…Further study is needed to fully understand the active components in WG that synergistically act on chondrocyte hypertrophy related OA. However, hypertrophy involves morphologic changes such as enlargement of cells with an increase in apoptotic rate [81]. An in vivo study with morphological evidence may have strengthened our results.…”
Section: Discussionsupporting
confidence: 67%
“…Several reviews have highlighted the similarity of chondrocyte hypertrophy observed in OA and transient cartilage differentiation [ 8 , 28 , 29 ]; thus, in this article, we will only briefly discuss the resemblance of these two processes.…”
Section: Chondrocyte Hypertrophy In Oamentioning
confidence: 99%
“…Angiogenesis plays a crucial role in initiating chondrocyte hypertrophy; therefore, the timely and controlled delivery of bioactive factors to promote vascularization is essential for this process. However, direct loading of water-soluble compounds into hydrogels often results in a burst release that is difficult to synchronize with the spatiotemporal rhythm of ECO . To address this challenge, biodegradable microspheres (termed as M) made of aliphatic polyesters, such as poly­(lactide- co -glycolide) (PLGA), have been extensively studied as drug carriers in various biomedical applications, offering sustained release capabilities .…”
Section: Introductionmentioning
confidence: 99%